Managing complications of radiation therapy in head and neck cancer patients: part I. management of xerostomia - Ngeow, Wei Cheong; Chai, Wen Lin; Rahman, R.A.; Ramli, R. (2006)
Head and neck cancer is becoming a more recognizable pathology to the general population and dentists. The modes of treatment include surgery and/or radiation therapy. Where possible, pretreatment dental assessment shall be provided for these patients before they receive radiation therapy. There are occasions, however, whereby head and neck cancer patients are not prepared optimally for radiation therapy. Because of this, they succumb to complicated oral adverse effects after radiation therapy. Part I of this series reviews the management of xerostomia. The management of the effect of xerostomia to the dentition/oral cavity is discussed in Part II.